Pengaruh Total Assets Turnover & Gross Profit Margin, terhadap Struktur Modal pada Perusahaan Sub Sektor Logam dan Mineral yang Terdaftar di BEI - Jordi Alfayer; Nafisah Nurulrahmatiah; Juwani Juwani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of Total Assets Turnover (TATO) and Gross Profit Margin (GPM) on Capital Structure in metal and mineral sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Capital structure is a crucial aspect of corporate finance as it relates to funding policy and financial risk. The research method employed is quantitative with a multiple linear regression approach. Data were obtained from the annual financial reports of the selected companies. The analysis results show that, partially, Total Assets Turnover has a negative and significant effect on capital structure, while Gross Profit Margin has a positive and significant effect. Simultaneously, both independent variables significantly influence the capital structure. These findings indicate that asset utilization efficiency and gross profitability play essential roles in determining capital structure policy. Therefore, company management is advised to continuously improve operational efficiency and profitability to achieve an optimal and sustainable capital structure.